PEMANFAATAN ABU SEKAM PADI SEBAGAI PENGGANTI SEMEN PADA METODA STABILISASI TANAH SEMEN - Idharmahadi Adha (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
Sub base course and base course are the layers under the surface course. Generally, materials of sub base course or base course are fine aggregates and coarse aggregates. But some locations in field, sometimes can not be found the aggregates to use as the material construction. Portland cement is always used as the additive material in soil stabilization method, but cost of portland cement is very high. One of the solution is used mixture of rice husk ash and portland cement as the additive material to stabilized of soils. The result of research, showed that mixing of rice husk ash material and portland cement can be able to increase of soil plasticity properties and bearing capacity and shear strength of soils. Based on testing of bearing capacity at 9% prosentage of rice husk ash material and portland cement, with curring time in 28 days, can be recommended that soil stabilization be used as base course in pavement structure of highway engineering, where CBR Laboratory value is 120% in unsoked CBR and 102% in soaked CBR.